Regulatory capital is a panacea for efficiency, credit growth and reducing non-performing loans in commercial banks / Amina Malik …[et al.] - Malik, Amina; Butt, Babar Zaheer; Ud Din, Shahab; Aziz, Haroon (Universiti Teknologi MARA, 2021)
This study examined the effectiveness of regulatory capital in enhancing efficiency and credit growth and reducing bad loans in commercial banks listed on the Pakistan Stock Exchange (PSX) from 2010 to 2019. Precisely, the impact of capital adequacy ratio (CAR) was studied on net interest margin (NIM), credit growth (CR) and non-performing loans (NPLs). The impact of capital adequacy regulations was assessed by retrieving data from financial statements analysis (FSA), Bank Financial statements and the World Bank website. Panel regression models including ordinary least squares (OLS), fixed and random effects under robust title were applied in this study. Results revealed that the implementation of stringent CAR plays the role of panacea and increases interest margin & credit growth and a reduction of NPL in Pakistani commercial banks. The study provides practical results for regulators to customize regulations on credit growth to reduce non-performing loans and maintain healthy growth of loans by not compromising on interest margins as well as maintenance of minimum capital adequacy ratios. With the high significance of stringent minimum capital adequacy for banks, the findings of the study are valuable for regulators, banks, auditors and investors, as capital adequacy ratio commonly plays the role of Panacea in terms of efficiency, credit growth and reduction in non-performing loans.